Comparison of Tunneling Characteristics in the MTJs of CoFeB/MgO/CoFeB with Lower and Higher Tunneling Magnetoresistance - Choi, G. M.; Shin, K. H.; Seo, S. A.; Lim, W. C.; Lee, T. D. (KOREAN MAGNETICS SOC, 2009)
We investigated the I-V curves and differential tunneling conductance of two, CoFeB/MgO/CoFeB-based, magnetic tunnel junctions (MTJs): one with a low tunneling magnetoresistance (TMR; 22%) and the other with a high TMR (352%). This huge TMR difference was achieved by different MgO sputter conditions rather than by different annealing or deposition temperature. In addition to the TMR difference, the junction resistances were much higher in the low-TMR MTJ than in the high-TMR MTJ. The low-TMR MTJ showed a clear parabolic behavior in the dI/dV-V curve. This high resistance and parabolic behavior were well explained by the Simmons' simple barrier model. However, the tunneling properties of the high-TMR MTJ could not be explained by this model. The characteristic tunneling properties of the high-TMR MTJ were a relatively low junction resistance, a linear relation in the I-V curve, and conduction dips in the differential tunneling conductance. We explained these features by applying the coherent tunneling model.
Keywords: JUNCTIONS; SPECTRA